PERLINDUNGAN HUKUM TERHADAP PENGETAHUAN KULINER TRADISIONAL INDONESIA (RENDANG) BERDASARKAN ASPEK PERDAGANGAN HAK KEKAYAAN INTELEKTUAL (TRIPS): LEGAL PROTECTION OF INDONESIAN TRADITIONAL CULINARY KNOWLEDGE (RENDANG) BASED ON THE TRADE-RELATED ASPECTS OF INTELLECTUAL PROPERTY RIGHTS (TRIPS) - Vania Rakhmadhani; Harisman (Universitas Majalengka, 2026)
Traditional knowledge in the culinary field constitutes a form of communal intellectual property containing significant cultural, social, and economic values for Indonesian society. One prominent example is rendang, originating from Minangkabau traditions and recognized internationally. This research aims to examine legal protection for Indonesian culinary traditional knowledge under the Trade Related Aspects of Intellectual Property Rights (TRIPS) Agreement, and to analyze the legal implications of Malaysia's claim over rendang. Using normative legal research methods supported by primary, secondary, and tertiary legal materials, the results indicate that although TRIPS has been ratified through Law No. 7 of 1994, protection of traditional knowledge in Indonesia still faces significant obstacles including limited legal regulations, weak law enforcement, and low public awareness. National inventory of communal intellectual property is identified as a crucial step to document and strengthen the legal basis for Indonesia's traditional knowledge, including through international recognition via UNESCO.